Case report: a case report of excision of giant lipoma in the posterior neck - Du, Aichao; Wang, Hongyu; Dai, Junqiang; Dong, Qiang; Yuan, Guoqiang; Pan, Yawen (Frontiers in Oncology, 2024)
Lipomas, benign tumors originating from the anomalous proliferation of adipocytes, predominantly emerge in regions rich in adipose tissue. However, their presence in the head and neck areas remains rare, constituting approximately 13% of all diagnosed lipoma cases. This study presents a case involving a substantial subcutaneous lipoma located at the posterior neck, measuring about 20 cm × 19 cm × 10 cm. The patient presented with swelling and pain in the back of the neck. And the considerable dimensions of this lipoma significantly impacted the patient’s quality of life and aesthetic appearance. Concurrently, the patient exhibited symptoms indicative of degenerative cervical spine disease and cervical disc herniation. After admission, a comprehensive examination, including ultrasound, CT scan, and MRI, was conducted. Given the clinical complexity, the decision for surgical intervention was deemed essential. The surgical strategy entailed a meticulous total excision of the tumor through an incision made in the posterior cross-neck, coupled with the strategic removal of excess skin. To facilitate wound healing, postoperative management included the use of negative pressure drainage. Pathological examination conclusively identified the mass as a lipoma. Postoperative follow-ups indicated successful recovery, as evidenced by the restoration of the neck’s aesthetic contour and the complete resolution of the previously observed restrictions in sagittal neck movement.